(untitled) (Research, Society and Development, 2022)
Civil construction is one of the fields that produce the most large-scale undertakings, and is also one of the greatest causes of environmental impacts, due to the enormous consumption of natural resources in the production of raw materials for construction works and, also, what else discards and accumulates solid waste, causing economic, social and environmental damage to society, such as change of soil and vegetation, increased energy costs, high demand for water and emission of polluting gases that contribute to the growth of the greenhouse effect. In this scenario, to minimize the impacts caused to the environment, many studies are being directed to the recycling of Construction and Demolition Waste (CDW). The use of CDW is relevant for civil construction since it has several positive results, including not only the profitability but also the mechanical capacity of these elements with high percentages of reuse, which further reinforces the importance of developing sustainable means. This study aims to analyze the use of sustainable concrete in construction in general, highlighting the main advantages and disadvantages of applying this technology in civil construction. The adopted methodology was based on a review of the literature, with the aim of obtaining more information about the study between the period from 2011 to 2022. Based on the results obtained in the literature, it was possible to demonstrate that the use of concrete recycling is a sustainable method, and a very important alternative in civil construction, however, there are still few incentives and quality control of this material. Thus, the need for further studies on the subject is evident, to disseminate the use of recycled concrete in buildings.